(untitled) (European Journal of Behavioral Sciences, 2024)
Friendship contributes to mental well-being, is a protective factor in victimization and a challenge for children and adolescents with High Functioning Autism (HFA). The quantity and quality of their friendships depends on the quality of interventions in their environment. This study aims to investigate the quantity and quality of friendships between children with (AHF) and their peers in primary school, and the relationship between friendships and inclusive educational practices. The research sample consisted of 143 teachers of students with AHF in primary school. The qualitative approach used the Autism Inclusion Questionnaire (AIQ), while the quantitative approach used the Questionnaire on friendships between children with AHF and peers. Inferential statistics, i.e., the use of the x2 correlation test and Pearson’s coefficient, was used to investigate the association and type of association between friendship practices with AHF and educational, behavioral practices. Results showed that 35% of teachers believed that children with ASD tended to have no friends and were surrounded by loneliness. Only one third of them had a good friend. However, these friendships could not be considered meaningful as they were not characterized by reciprocity and common interests. 19 out of 37 educational inclusion practices were linked to the development and improvement of friendships. They can be useful for educators, practitioners and families at this age stage.